2006
DOI: 10.1007/s00540-006-0413-x
|View full text |Cite
|
Sign up to set email alerts
|

Omission of fentanyl during sevoflurane anesthesia decreases the incidences of postoperative nausea and vomiting and accelerates postanesthesia recovery in major breast cancer surgery

Abstract: Omission of fentanyl during sevoflurane anesthesia, combined with diclofenac and local infiltration anesthesia, decreases the incidences of postoperative nausea and vomiting and accelerates postanesthesia recovery in patients undergoing major breast cancer surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 25 publications
(68 reference statements)
1
36
0
1
Order By: Relevance
“…The scientific evidence that is available today allows us to affirm that the goal of achieving an adequate postoperative analgesia comfort and PONV is only achieved with the use of analgesic techniques that are balanced or use multiple methods, which covers drugs such as paracetamol, the NSAIDs, the infiltration of the surgical wound and peripheral nerve blocks (PNB). The use of opiates increases the incidence of PONV (13). Complications of soft tissue, bone, joint and nerve tissues are also rare.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific evidence that is available today allows us to affirm that the goal of achieving an adequate postoperative analgesia comfort and PONV is only achieved with the use of analgesic techniques that are balanced or use multiple methods, which covers drugs such as paracetamol, the NSAIDs, the infiltration of the surgical wound and peripheral nerve blocks (PNB). The use of opiates increases the incidence of PONV (13). Complications of soft tissue, bone, joint and nerve tissues are also rare.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is reported that the use of fentanyl in an ambulatory surgery setting increases PONV and delays post anesthesia recovery [2]. Because the opioid remifentanil is known for its extremely short half-life [10], it is reasonable to assume that its use would be associated with reduced opioid-related side-effects, such as PONV.…”
Section: Discussionmentioning
confidence: 99%
“…A written informed consent for data collection was preoperatively obtained from each of the patients. Exclusion criteria were as follows: all cases without the 100 mm visual analog scale (VAS) or verbal numerical rating scale (VNRS) for nausea within 24 h after the operation by any reasons [2,8]. All the case that met the exclusion criteria were excluded from further analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations